Determining of Coefficient Correlation between UCS and PLI data for Various Rock Types at Batu Hijau Mine PT Amman Mineral Nusa Tenggara - Adriansyah, Yan; Zakaria, Zufialdi; Muslim, Dicky; Hutabarat, Johanes (Faculty of Geological Engineering, Universitas Padjadjaran, 2017)
AbstractThe Batu Hijau Mine is one of the biggest gold-copper producer in Indonesia which operated by PT Amman Mineral Nusa Tenggara (PTAMNT). The mine site is located in the southwest corner of Sumbawa Island in the Sunda-Banda Archipelago in Indonesia. Based on the tectonic plate perspective, the Sumbawa Island lies along the tectonically active rock sequences.Refers to the geological model from comprehensive study starting from the exploration up to exploitation stages, there are four rock types that formed the slope at Batu Hijau Mine, namely volcanic rock, diorite, tonalite and young tonalite. The volcanic rock as a host rock is the most dominant material among the other rocks type which expose on the north-west, west and south wall.This study was focused on determining of the index conversion factor of the relation between uniaxial compressive strength (UCS) and point load test (PLT) data which obtained from the laboratory test result. The correlation factor for predicting UCS value from the PLT data for each rock type has shown the good correlation with the average of regression value is 0.88. Keywords : Batu Hijau, Uniaxial Compressive Strength, Point Load Test, Conversion Factor.